2019
DOI: 10.1088/1757-899x/648/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

3D Modelling Intestine Anatomy with Augmented Reality for Interactive Medical Learning

Abstract: Humans, one of the heterotrophic living things must meet energy needs by consuming food. The food is then described in the digestive system to become an energy source. The digestive system is composed of the digestive tract and digestive gland glands. In the excerpt of the book “Prometheus” human anatomy, the digestive tract acts as a tool for receiving, chewing, delivering, storing, digesting, absorbing (absorbing) and eliminating food. The small intestine, large intestine, and rectum are organs included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The 3D model's heart, stomach, and esophagus are interactive touches on the screen. The model interacts to display the pertinent data for the selected organ or organ system [15]. The process of assembling or combining all developed assets is part of the development of the application.…”
Section: Results and Outcomesmentioning
confidence: 99%
“…The 3D model's heart, stomach, and esophagus are interactive touches on the screen. The model interacts to display the pertinent data for the selected organ or organ system [15]. The process of assembling or combining all developed assets is part of the development of the application.…”
Section: Results and Outcomesmentioning
confidence: 99%
“…The test also included tilt detection to determine the distance with a camera tilt test. Research has confirmed that the most stable detection angle is between 45 and 150 degrees (Subhashin et al, 2020;Andayani et al, 2019).…”
Section: Examples Of Displaying 3d Graphic Content On Mobile Devicesmentioning
confidence: 96%
“…Another alternative is various printed media, which are mainly used to facilitate the learning of the material. In addition to the graphic content it contains, the augmented paper also serves as an image target that enables the display of augmented reality on a smart device, such as a 3D model or other multimedia content (Wikipedia, 2021;Dijaya et al, 2018;Chow, & Sharmin, 2020;Subhashin et al, 2020;Andayani et al, 2019). On mobile devices, the thing works best via a developed application where the display is based on the model method of representing data (Kipper & Rampolla, 2012).…”
Section: Examples Of Displaying 3d Graphic Content On Mobile Devicesmentioning
confidence: 99%
“…Using 3D augmented reality technology will result in an appealing application for the user. For example, a previous study has used augmented reality to create a 3D picture of the gut for anatomical purposes (Andayani et al, 2019). This result could help the doctors or students explain to the patient if needed for more closure.…”
Section: Ar Learning Environmentmentioning
confidence: 99%